EVALUATION OF ANTI-ASTHMATIC ACTIVITY OF METHANOLIC EXTRACT OF BERLERIA PRIONITIS LINN. AERIAL PARTS - S., Manekar Snehal; S., Charde Manoj (International Journal of Current Pharmaceutical Research, 2018)
Objective: The aim of the present study is to evaluate the aerial parts of a plant of Barleria prionitis Linn., for its antiasthmatic activity with the separation of active moieties. Methods: Adult wistar albino rats were used for the anti-inflammatory study. Histamine-induced bronchospasm was conducted on isolated goat trachea. Results: The dried and powdered aerial parts of Berleria prionitis was extracted with continuous soxhlet extraction with Petroleum ether (40-60 Â° C), Chloroform, Ethyl acetate, Acetone, Methanol, and Hydroalcoholic solvents. Preliminary phytochemical screening of all extracts was done. Preliminary animal studies by In vitro isolated goat trachea chain preparation of all extracts were done to find out the potent extract. In this study, the methanolic extract of aerial parts of Berleria prionitis was found to be potent comparative to another extract. The results of carrageenan induced rat paw oedema model indicated the dose-dependant anti-inflammatory activity. As compared to standard drug (Indomethacin), methanolic extract showed similar activity which was found to be statistically significant (P<0.0001). The extent of DPPH radical scavenging was determined by calculated the IC50 value of methanolic extract Berleria prionitis (133.5) compared with the Ascorbic acid (114.7) taken as standard. In the present study, the histamine-induced dose-dependent contraction of goat tracheal chain was significantly inhibited (p<0.001) by methanolic extract of aerial parts of Berleria prionitis (200 Î¼g/ml). Thus the present study revealed that the methanolic extract of Berleria prionitis (MEBP) has significant antihistaminic (H1 receptor antagonist) activity. Conclusion: In view the fact that tribal have well experienced the antiasthmatic effects of the roots of Barleria prionitis Linn. The results of our study, for the first time, show that the methanolic extract of aerial parts of Berleria prionitis Linn. possesses antioxidant, anti-inflammatory, Bronchodilator properties and therefore can be used for the antiasthmatic treatment.